DEMONETIZATION AND IMPROVISATION OF VALUE CHAIN DYNAMIC IN AFGHANISTAN: AN EXPLORATORY STUDY - Panah, Abdul Masood; Muniraju, Y. (International Journal of Accounting & Finance Review, 2020)
Demonetization is the elimination of the backing of the money granted by law to the notes is, therefore, legal tender. On Wednesday_ September 2002, the new president of the transition government announced from television to the people of Afghanistan that the decision had been reached in response to Afghan and foreign experts. They had advised the new Government to replace the currency and reform Afghanistan’s banking system. “This will help in controlling the massive inflation and stabilize the economy. A survey was conducted with a pre-tested questionnaire among the common public in Kabul and Parwan’s main two provinces to collect their views on factors associated with demonetization in Afghanistan. PCA (Principal component analysis) technique has been used for factor extraction and dimension reduction using the Varimax orthogonal rotation. The top key factors related to the implementation of demonetization have been identified as socio-economic factors, public hardships, challenges, and implementation challenges. The survey data’s descriptive analysis shows that most survey respondents either ‘strongly agree’ or ‘agree’ with the 19 measures on perception and opinion of the common man (general public) on demonetization in Afghanistan.